Dingxin Recipe IV attenuates atherosclerosis by regulating lipid metabolism through LXR-α/SREBP1 pathway and modulating the gut microbiota in ApoE-/- mice fed with HFD. (10th February 2021) - Zhang, Yaxin; Gu, Yuyan; Chen, Yihao; Huang, Zhiyong; Li, Mei; Jiang, Weihao; Chen, Jiahui; Rao, Wenting; Luo, Shangfei; Chen, Yuyao; Chen, Junqi; Li, Lijun; et al.
Abstract: Ethnopharmacological relevance: Dingxin Recipe (DXR) is a traditional Chinese medicine formula that has been reported to be effective and safe treatment for cardiovascular diseases, such as arrhythmias, coronary heart disease. Dingxin Recipe IV (DXR IV) was further improved from the DXR according to the traditional use. However, the mechanism of DXR IV in atherosclerosis is unclear. Aim of the study: This study aimed to illustrate whether DXR IV improve atherosclerosis through modulating the lipid metabolism and gut microbiota in atherosclerosis mice. Materials and methods: 40 male ApoE -/- mice were fed on HFD for 12 weeks and were then treated with DXR IV (1.8, 0.9, or 0.45 g/kg/d) for another 12 weeks. The decroation of DXR IV contains four traditional Chinese medicines: the dried rhizome of Coptis chinensis Franch. (15.09%), the root of Salvia miltiorrhiza Bunge (28.30%), the seed of Ziziphus jujuba Mill. (37.74%) and the fruiting body of Ganoderma lucidum (Leyss.ex Fr.) Karst. (18.87%). 8 male c57BL/6 mice fed a normal diet served as control group. The atherosclerotic plaque was quantified by oil-red O staining and masson trichrome staining. Mice feces were collected. The gut micobiota were detected by 16S rRNA gene sequencing and fecal metabolites were analyzed by 1 H NMR spectroscopy. The effect of DXR IV on blood lipids (TG, TC, LDL-C, HDL-C) was investigated. The lipid metabolism related genes were determined by RT-qPCR and western blotting respectively. Results: DXR IV exerted the anti-atherosclerosis effect by inhibiting the excessive cholesterol deposition in aorta and regulating the level of TG, TC, LDL-C and HDL-C. The composition of gut microbiota was changed. Interestingly, the relative abundance of Muribaculaceae and Ruminococcaceae increased after DXR IV administration, whereas the abundance of Erysipelotrichaceae decreased, which have been beneficial to lipid metabolism. Nine potential metabolic biomarkers, including acetate, butyrate, propionate, alanine, succinate, valerate, xylose, choline, glutamate, were identified, which were related to fatty acid metabolism. Further, the pathway of fatty acid was detected by the RT-qPCR and western blotting. Compared with model group, the level of LXR-α and SREBP1 decreased significantly in DXR IV group while LXR-β, SREBP2 showed no statistical significance. It indicated that DXR IV modulated lipid metabolism by LXR-α/SREBP1 but not LXRβ and SREBP2. Conclusions: DXR IV exhibits potential anti-atherosclerosis effect, which is closely related to lipid metabolism and the gut microbiota. This study may provide novel insights into the mechanism of DXR IV on atherosclerosis and a basis for promising clinical usage. Graphical abstract: Image 1